The Elephant in the Room: NAMUDNO, Shelby County, and Racially Polarized Voting - Richard L. Engstrom (Transatlantica)
A key provision of the Voting Rights Act was rendered ineffective by the U.S. Supreme Court in a 5 to 4 decision in 2013. The provision, focused primarily on governments in the South, required them to gain federal “preclearance” for changes in their election arrangements before they could be implemented. Preclearance was designed to block retrogressive changes. In the latest renewal of that provision, in 2006, Congress identified the problem of minority vote dilution as the major reason preclearance needed to be continued. It further found that protected minorities were vulnerable to dilutive elective schemes because of the pervasive presence of racially polarized voting (RPV) in those jurisdictions. This essay examines the extensive evidence of RPV relied upon by Congress but ignored by the Court majority and also the legal import of this evidence as identified in numerous briefs before the Court, also ignored by the majority.